Knowledge Management and Organizational Learning In Organizational Development - Tini Mogea (Populer: Jurnal Penelitian Mahasiswa, 2023)
Globalization has required humans to be constantly adaptable and competitive. Similarly, organizations must be more adaptable, resilient, able to change direction quickly, and capable of managing globally competitive human resources (HR). The availability of competitive and qualified human resources, as well as science and technology, is critical as an organizational asset for developing and competing in the globalization era. Successful organizations consistently generate new knowledge and are able to disseminate it throughout their organization while quickly adapting it to information technology and their products and services. Knowledge Management evolves as an important and strategic component of the organization in order to create value, improve organizational effectiveness and productivity, and boost organizational competitiveness.